"Rx - The mistakes we make!!": A short study - Arun Rathnam; Nidhi Madan (Wolters Kluwer Medknow Publications, 2011)
Context: There is concern regarding the irrational production, prescription and use of drugs in India. Aim: This study aimed to describe the quality of prescriptions by dental practitioners of one particular college in a short period of time. Materials and Methods: A survey of all prescriptions dispensed from the various departments of K.L.E.S.'s Institute of Dental Sciences, Belgaum, Karnataka, was conducted by collecting them from the patients exiting the college premises. The prescriptions were photocopied and handed back to the patients. The samples were collected over a period of 7 days. The samples were then analyzed for their content based on an ideal prescription format and the results were tabulated. Results: The findings of the study suggest that most of the prescriptions given are woefully inadequate in content. Conclusions: It can be concluded that a clear policy about the standard of prescriptions and periodic internal monitoring is the answer for quality prescriptions. Computerization of the prescription format is also a thought-provoking alternative.